Factors Affecting Financial Management Behavior Among Universitas Tarumanagara’s Students - Mardiana Mardiana; Sawidji Widoatmojo (International Journal of Application on Economics and Business, 2023)
This research aims to determine the effect of financial knowledge, financial attitude, and income on financial management behavior in Universitas Tarumanagara’s students. The population of this study was active students at Universitas Tarumanagara that selected using a non-probability sampling technique, which is purposive sampling amounted to 150 respondents. The data collection using questionnaires presented in the form of a google form and distributed online. The data obtained were processed using PLS-SEM using Smart-PLS software. The results found that financial knowledge has a positive significant influence on financial management behavior, a financial attitude has a positive significant influence on financial management behavior. Meanwhile, income has a positive insignificant influence on financial management behavior.